Minireview: The Versatile Roles of Lysine Deacetylases in Steroid Receptor Signaling - Kadiyala, Vineela (Mol Endocrinol, 2014)
Lysine deacetylases have been known to regulate nuclear receptor function for many years. In the unliganded state, nuclear receptors that form heterodimers with retinoid X receptors, such as the retinoic acid and thyroid hormone receptors, associate with deacetylases to repress target genes. In the case of steroid receptors, binding of an antagonist ligand was initially reported to induce association of deacetylases to prevent activation of target genes. Since then, deacetylases have been shown to have diverse functions in steroid receptor signaling, from regulating interactions with molecular chaperones to facilitating their ability to activate transcription. The purpose of this review is to summarize recent studies on the role of deacetylases in steroid receptor signaling, which show deacetylases to be highly versatile regulators of steroid receptor function.